Utilization Pattern of Long-Acting and Permanent Family Planning Methods and Associated Factors: A Community-Based Cross-Sectional Study in Ethiopia - Demeke CA; Kasahun AE; Belay WS; Chekol AN; Getaneh RA; Yimenu DK (Dove Medical Press, 2020)
Chilot Abiyu Demeke,1,* Asmamaw Emagn Kasahun,1,* Wudneh Simegn Belay,1 Abay Nega Chekol,2 Rahel Alemu Getaneh,2 Dawit Kumilachew Yimenu1 1Department of Pharmaceutics and Social Pharmacy, School of Pharmacy, College of Medicine and Health Sciences, University of Gondar, Gondar, Amhara Regional State, Ethiopia; 2School of Pharmacy, College of Medicine and Health Sciences, University of Gondar, Gondar, Amhara Regional State, Ethiopia*These authors contributed equally to this workCorrespondence: Dawit Kumilachew Yimenu Department of Pharmaceutics and Social Pharmacy, School of PharmacyCollege of Medicine and Health Sciences, University of Gondar, Gondar, Amhara Regional State, EthiopiaEmail dawitkumilachew@yahoo.comBackground: Long-acting and permanent family planning methods (LAPMs) are modern contraceptive methods that can prevent pregnancy for greater than one year and include long-acting reversible contraceptive methods (LARCs) (Intrauterine device and subdermal implants), and permanent contraceptive methods (Tubal ligation and Vasectomy). The current study aimed to assess the utilization pattern of long-acting and permanent contraceptive methods and factors associated with their utilization in Lay-Armachiho district, Amhara regional state, Ethiopia.Methods: A community-based cross-sectional study was conducted. Data were collected by using an interview method and the collected data were entered and analyzed using Statistical Package for Social Sciences (SPSS) version 20. Both binary logistics and multivariable logistic regression analyses were used to analyze predictive variables with the utilization of contraceptives. A 95% confidence interval (CI) and a P-value of < 0.05 were used to declare statistical significance.Results: A total of 460 women have participated in the study. The proportion of women that utilize long-acting and permanent contraceptives was found to be 65.4%. Educational statuses, residence, attitude towards long-acting contraceptives, discussion, and joint decision-making with their spouse were factors significantly associated with the utilization of long-acting contraceptive methods.Conclusion: The current study showed that there is high utilization of LAPMs. Women’s attitude, educational status, residency, frequent discussions, and a joint decision with their partners about LAPMs were significantly associated with the utilization of long-acting and permanent contraceptives. There is a significant impact of husbands (sexual partners) on the utilization and choice of contraceptive methods by women.Keywords: contraceptive, long-acting, fertility, maternal health, family planning